PENGEMBANGAN KOMIK IPS TEMA KEGIATAN EKONOMI SEBAGAI MEDIA PEMBELAJARAN UNTUK SISWA KELAS VII - Marwiyah Marwiyah; Triani Ratnawuri (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2018)
The purpose of this research is to make an IPS comic with the theme economic activity as the learning media that suitable for VII Grade of SMP Negeri 04 Metro. This research used 4D development model (Define, Design, Develop, and Dissemination). However, this research just as for as develop step. In this research, the researcher did not use Dissemination step because of limited time and expense. In the first step, the researcher analyzed the students needed by doing pre-survey at SMP Negeri 4 Metro. Next, the researcher made the design of Keywords: Developing, Learning Media, IPS Comicproduct such as making learning comic with the topic economic activity. The result of product that made by the researcher will be validated by the expert of learning media, the expert of topic and language. For the next, this research was tested to a little group consist of 10 students from VII B SMP Negeri 4 Metro. The result of the value validation percentage for the expert of learning media is 93%, the expert of topic 88%,the expert of language 96% and value tasted from the little group is 94,6%. So, it can be concluded that comic with the topic economic activity is very reasonable to use for the students as the IPS learning media with the topic economic activity for VII Grade at SMP.